Synthesis of brushite/polyethylene glycol cement for filler in bone tissue injuries - Morúa,O. C. (2021)
Abstract The objective of this work was to produce brushite cement for orthopedic applications, based on the system wollastonite/phosphoric acid with the incorporation of polyethylene glycol (PEG) as a setting and processing additive. Brushite/PEG cement was obtained by the dissolution-precipitation method and its physicochemical properties were characterized by X-ray diffraction, compressive strength, porosimetry, and biological behavior (cell adhesion and bioactivity tests). The results indicated the formation of brushite cement with 21.4 MPa of compressive strength and 30% porosity, similar to human trabecular bone. The surface was shown to be adequate for cell adhesion and growth and bioactive with the formation of apatite layers. The incorporation of PEG improved working conditions without causing undesirable changes in the physicochemical properties and biological behavior of developed cement, thus promising for the repair of bone tissue injuries.